A comparative study of indexes used for litter pollution assessment in urban and public environments - Maryam Delavari Heravi; Mahdieh Haddadi; Farzaneh Karami Nejad; Zahra Izadi Yazdanabadi; Gholam Ali Haghighat (Heliyon, 2024)
Litter is a common pollution in the urban environment and public places such as beaches, which has serious health and economic consequences. Several indexes are used to interpret the pollution status caused by litter, which have different limitations and strengths. In this review, the efficiency and characteristics of different indexes were compared. For this purpose, related articles were searched in Scopus, PubMed, and Web of Knowledge, and after screening, 21 articles were selected. The main questions of this study included factors affecting the interpretation of pollution in different indexes and the criteria considered in each index. The results showed that the existing indexes based on the type of litter include two categories of comprehensive indexes such as Clean Environment Index and specific indexes such as Cigarette Butt Pollution Index. Also, the index can be divided into two categories in terms of spatial application, including general indexes such as Environmental Status and specific indexes such as Clean Coast Index. An important difference in the indexes is the importance of the impact of the pollution potential of different litter in the assessment of the status in indexes such as Clean Environment Index and Environmental Status, while indexes such as Clean Coast Index evaluate the status based only on the density of litter. According to the capabilities of each of the indexes, it is necessary to pay attention to the local needs as well as the characteristics of each index in using in urban management plans.